Influenza dell’imprenditore e delle relazioni nel processo di internazionalizzazione dei birrifici artigianali - Francioni, Barbara (Piccola Impresa / Small Business, 2016)
The principal aim of this study was to investigate how owner-managers practise internationalization in Italian small breweries from Pesaro-Urbino province. Results permit to identify four alternative approaches in which owner-managers understand and practice internationalization, which consequently generates diversity in the management of international activities. Results also revealed that in the majority of cases the decision to start exporting was unplanned: they relied mostly on contacts created through trade fairs or friends/relatives.